INNOVATIVE DEVELOPMENT OF EXHAUST FAN WITH SMART GAS DETECTOR SYSTEM POWERED BY ARDUINO UNO FOR WELDING WORKSHOP SAFETY ENHANCEMENT - BINTI IDRIS, NUR FARAHAIZAN; ABDUL RAZAK KHAN, NURUS SADIQIN; KASIM, KHAIRULNIZAM (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
In welding workshops, gas leaks pose serious safety risks, including potential fires and explosions. This research introduces a novel Exhaust Fan with Smart Gas Detector System designed to enhance safety through Arduino Uno technology. The study focuses on developing an automated, reliable system for detecting hazardous gas leaks, activating an exhaust fan for gas removal, and providing user notifications both on-site and remotely. The system integrates an MQ5 gas sensor for detecting dangerous gases, an Arduino Uno microcontroller for data processing and system control, and a motorized exhaust fan for effective gas extraction. The effectiveness of the system was tested under controlled conditions, demonstrating its ability to detect gas leaks in real time, activate the exhaust fan, and alert users. This development represents a significant advancement over traditional gas detection methods by combining real-time detection, automated response, and remote notifications. This innovative approach offers a scalable, cost-effective solution for improving safety in welding workshops and sets the stage for future advancements in industrial safety technologies